GAMBARAN STATUS GIZI PADA PASIEN TUBERKULOSIS PARU (TB PARU) YANG MENJALANI RAWAT INAP DI RSUD ARIFIN ACHMAD PEKANBARU - Wina Astari Putri; Sri Melati Munir; Erwin Christianto (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTTuberculosis (TB) is still one public health problem in the world. In2014, 9.6 million people fell ill with TB and 1.5 million died from the disease.Nutritional status is a state body as a result of food consumption and the use ofnutrients. TB may affect nutritional status then cause malnutrition andmalnutrition may increase TB progress. Undernutrition is prevalent in about 25-40% of hospitalized patient and is associated with higher care complexity, longerlength of stay, and increased morbidity and mortality. This study was usingdescriptive methods with cross sectional approached. The sampling techniqueused minimal sampling. The study was held on February – March 2016 withnumber of sample is 36 person whom pulmonary tuberculosis inpatient atpulmonary hospitalization room of Arifin Achmad general hospital. The result ofthe study is characteristic based on gender showed 26 (72,2%) persons are male,24 (66,7%) persons are 18-55 years old. Characteristic based on occupationshowed 9 (25%) persons were unemployment. 22 (61,1%) persons is alreadyconsume OAT less than 2 months and 19 ( 52.8 % ) persons had a decrease inappetite . Most nutritional status based on BMI is underweight by 22 ( 61.1 % )persons , most nutritional status based on LLA was 15 ( 41.7 % ) personsclassified as malnutrition and highest MUST score was 31 ( 86.1 % ) personsclassified as high risk .Keywords : pulmonary tuberculosis inpatient, nutritional status , MUST